The Effect of Profitability, Leverage, and Asset Growth on Company Value - Alexander Purba; Cahyaningsih Cahyaningsih; Wiwin Aminah (Green Publisher Indonesia, 2025)
The value of a company reflects its achievements and public trust over time, represented by the price agreed upon in buy-sell transactions. An increase in stock prices enhances company value and investor profits. Indonesia's manufacturing industry, covering diverse sectors like chemicals and consumer goods, has shown consistent growth, particularly in the pulp and paper sub-sector. Both Indonesia and Brazil have unique advantages for efficient pulp production, with the pulp and paper export sector reaching 7.5 billion in 2021. A company's value mirrors investor sentiment about its performance and future prospects, while rising stock prices indicate increasing company value, influenced by various market factors. This study uses research methode such a descriptive statistics, panel data regression, classical assumption tests, F-tests, R² for model explanation, and t-tests to assess the significance of independent variables. The finding of this paper is profitability positively influences company value, while leverage negatively impacts it; additionally, asset growth significantly enhances dividend policy.